The land and people of Ceylon - Wilber, Donald Newton (Philadelphia : Lippincott, 1963)
An introduction to the land, natural resources, history, political structure, major industries, and people of this island nation off the southern tip of India.
Keywords: Sri Lanka -- Juvenile literature; Sri Lanka